Impact of Foreign Aid on Economic Development: A Critical Literature Review - Fitriani, Hana (Advances: Jurnal Ekonomi & Bisnis, 2024)
Purpose: This critical literature review explores the impact of foreign aid on economic development. It aims to analyze the existing studies in order to determine the relationship between foreign aid and economic development and identify any key patterns or inconsistencies in the findings. Study design/methodology/approach: The review adopts a systematic approach by conducting a comprehensive search of relevant academic articles and reports. The collected literature is then screened based on predetermined inclusion and exclusion criteria to ensure the selection of high-quality and rigorous studies. The findings from the selected studies are synthesized and analyzed to provide a comprehensive overview of the impact of foreign aid on economic development. Findings: The analysis of the reviewed studies reveals a complex and nuanced relationship between foreign aid and economic development. While some studies suggest a positive relationship by emphasizing the role of aid in promoting economic growth and reducing poverty, others highlight potential negative consequences, such as aid dependency and crowding out of domestic investment. Additionally, the effectiveness of aid is found to be heavily influenced by various contextual factors, including recipient country governance, policy frameworks, and aid allocation mechanisms. Overall, the findings indicate a need for a more targeted and context-specific approach to foreign aid to maximize its positive impacts on economic development. Originality/value: This literature review contributes to the existing body of knowledge by synthesizing a wide range of studies and providing a comprehensive understanding of the impact of foreign aid on economic development. By identifying key patterns and inconsistencies in the findings, this review offers valuable insights for policymakers, aid organizations, and researchers working in the field of international development. The examination of contextual factors and the call for a more targeted approach add depth to the understanding of the complex relationship between foreign aid and economic development, thereby advancing the discourse in this area.